From Values to Value: The Commensuration of Sustainability Reporting and the Crowding Out of Morality. (March 2023) - van Bommel, Koen; Rasche, Andreas; Spicer, André
Drawing on extensive case study evidence, this study unpacks sustainability reporting's evolution from a moral values–based practice toward a financialized value–based one. We argue that this transition can be seen as a commensuration project. We examine the dynamics of this process and its implications for sustainability-related outcomes. We find that increased levels of commensuration have moved sustainability reporting away from an original emphasis on morality and values to a focus on strategic value creation for the firm. We theorize this process as a "crowding out of morality" that is enabled by a rigid cognitive framing of social and environmental issues (objectification) and the monetized coordination of relevant social interactions (marketization). We outline implications of our analysis for the scholarly debates on the institutionalization of sustainability reporting and commensuration.